(untitled) (Journal of Dhaka Medical College, 2017)
Introduction: In the present times, the emphasis on minimally invasive surgery has lead to a resurgence of interest and importance of vaginal Hysterectomy for non-prolapsed indications i.e. non decent vaginal Hysterectomy (NDVH) as the scar less Hysterectomy. It has several benefits over abdominal Hysterectomy in terms of cosmetic advantages, lesser post operatives morbidity and faster recovery. Objectives: The study was to compare and assess various factors like operative duration of surgery intra operative blood loss, intra operative and post operative complications, post operative analgesia requirement, post operative ambulation and duration of post operative hospital stay and to put forward best route of hysterectomy. Conclusions: Non-decent vaginal hysterectomy is a better alternative to abdominal hysterectomy in cases with benign pathology of the uterus, uterine size<14 weeks, uterus with good mobility and adequate vaginal access. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 72-73